Healthcare-associated infections in critical COVID-19 patients in Tunis: epidemiology, risk factors, and outcomes - Ahlem Trifi; Selim Sellaouti; Asma Mehdi; Lynda Messaoud; Eya Seghir; Badis Tlili; Sami Abdellatif (Acute and Critical Care, 2023)
Background Coronavirus disease 2019 (COVID-19) pandemic disrupted adherences to healthcare-associated infection (HAI) prevention protocols. Herein, we studied the characteristics of all HAIs occurring in critically ill COVID-19 patients. Methods A retrospective, single-center cohort of critical COVID-19 patients during 2021. Microbiological samples were collected if HAI was suspected. We analyzed all factors that could potentially induce HAI, using septic shock and mortality as endpoints. Results Sixty-four among 161 included patients (39.7%) presented a total of 117 HAIs with an incidence density of 69.2 per 1,000 hospitalization days. Compared to the prior COVID-19 period (2013–2019), the identification of HAI increased in 2021. HAIs were classified into ventilator-associated pneumonia (VAP; n=38), bloodstream infection (n=32), urinary tract infection (n=24), catheter-related infection (n=12), and fungal infection (n=11). All HAIs occurred significantly earlier in the post–COVID-19 period (VAP: 6 vs. 10 days, P=0.045, in 2017 and 2021). Acinetobacter baumannii (39.5%) and Klebsiella pneumoniae (27%) were the most commonly isolated pathogens that exhibited a multidrug-resistant (MDR) profile, observed in 89% and 64.5%, respectively. The HAI factors were laboratory abnormalities (odds ratio [OR], 6.4; 95% confidence interval [CI], 2.3–26.0), cumulative steroid dose (OR, 1.9; 95% CI, 1.3–4.0), and invasive procedures (OR, 20.7; 95% CI, 5.3–64.0). HAI was an independent factor of mortality (OR, 8.5; P=0.004). Conclusions During the COVID-19 era, the incidence of HAIs increased and MDR isolates remained frequent. A severe biological inflammatory syndrome, invasive devices, and elevated cumulative steroid dosages were related to HAIs. HAI was a significant death factor.